Coloured dissolved organic matter absorption of unfiltered samples from sea ice cores from the coastal zone of the southern Canadian Beaufort Sea, near Herschel Island - Qikiqtaruk - Fritz, Michael; Laux, Kristoffer; Juhls, Bennet (In: Fritz, M et al. (2025): Organic and inorganic geochemical properties of sea ice cores in the nearshore zone of the southern Canadian Beaufort Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984649, 2025)
For DOC and CDOM absorption, samples were filtered through a 0.7 μm glass fibre filter (Whatman GF/F syringe filter) which had been rinsed with 20 mL sample water. DOC samples were collected in 20 ml glass vials with septum lid, acifdified with HCl to pH < 2 and stored at 4°C until analysis. DOC was measured with a Shimadzu TOC-V analyzer. CDOM samples were collected in 100 mL amber glass bottles that were stored in the dark at 4°C until analysis. aCDOM was measured at the German Research Center for Geosciences (GFZ), Potsdam, Germany using a double beam LAMBDA 950 UV/Vis (PerkinElmer) spectrophotometer. The absorbance (A) was measured between 200 and 800 nm in 1 nm steps using a 5 cm cuvette. Absorption (a) was calculated from the resulting absorbance measurements via aCDOM(λ) = 2.303 * A(λ) / l, where l is the path length (length of cuvette in meter). Every 5 to 10 samples, the reference sample (Milli-Q water) was exchanged and a blank was measured to avoid instrument drift. Spectral slopes (S275-295, S350-400) as well as the Slope Ratio (SR = S275-295/S350-400) were derived using the linear regression slope of the log-transformed (natural logarithm) absorption spectra (Helms et al. (2008). Specific UV absorbance (SUVA) is defined as the UV absorbance of a water sample at a given wavelength normalized for dissolved organic carbon (DOC) concentration. SUVA254 is defined as the UV absorption at 254 nm divided by the DOC concentration measured in mg L-1 (Weishaar et al., 2003). Spectral slope, Slope Ratio and SUVA were only calculated for data from filtered samples as these parameters purely depend on dissolved matter properties. CDOM absorption spectra from unfiltered aliquots of the same sample might still be of interest as they provide insight into bulk optical properties, which are crucial for total absorption budgets and remote sensing algorithms that do not distinguish dissolved vs particulate absorption.
Keywords: Arctic; biogeochemistry; coloured dissolved organic matter (CDOM); dissolved organic carbon (DOC); Hydrogen isotopes; Oxygen isotopes; Permafrost; Sea ice; stable water isotopes; Suspended Particulate Matter (SPM)